ISLAM, (UN)CIVIL SOCIETY AND CHALLENGES FOR DEMOCRATISATION IN INDONESIA - Syaifudin Zuhri (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2022)
This article tries to critically examine the idea of civil society in light of Indonesia's Islamist politics. This raises the question of how far the idea of a civil society in a democratic country leads to public civility. This is an important question that must be addressed. The Majelis Mujahidin Indonesia (MMI) is the main focus of this article. MMI, one of the most active Islamist organizations founded after the fall of the authoritarian regime of the New Order, develops political frameworks that endanger democracy and public civility. MMI became an organization that advocates for uncivil discourses of Islamic interpretation, thus representing Indonesia's (un)civil society. It is most visible in the organization's views on democracy and its interpretation of the "jihad" doctrine. As a result, the article concludes that the classification of Indonesian civil society should include both civil and (un)civil society. In addition to civil society, Indonesia should include uncivil society, even if their orientation is different. An un-civil society threatens democracy and public civility while civil society is fighting for it.